Assessing the distribution of Piper porphyrophyllum (Sireh rimau) using species distribution model (SDM) in Kelantan, Peninsular Malaysia. Issue 1 (1st November 2022) - Zulkeflee, N H; Adek, N B Nek; Norzin, M A F; Awang, A; Ismail, N A; Daliman, S; Amaludin, N A
Abstract : Piper porphyrophyllum (Lindl.) N.E.Br. is one of the genera from the family Piperaceae. The local names for Piper porphyrophyllum are Sireh Rimau, Kerakap Rimau or Akar Bugu. P. porphyrophyllum was recorded in Machang and Jeli, Kelantan. and very common in the forests of Peninsular Malaya, but flowers are scarcely ever found. However, limited information on its distribution occurred in Kelantan. The objective of this study is to map the potential distribution of P. porphyrophyllum that occurs in Kelantan using the Species Distribution Model (SDM). During the survey, a total of five individuals and twelve individuals of P. porphyrophyllum were recorded respectively at Pulai Chondong, Machang and Lata Cuit, Jeli, Kelantan. The potential distribution of P. porphyrophyllum that occurred in Kelantan was mapped using the species distribution model (SDM) to predict their occurrence in Kelantan and mostly distributed in Jeli and Gua Musang. According to the Malaysia Plant Red List P. porphyrophyllum is listed as Not Evaluated (NE).